2019
DOI: 10.1007/s40843-018-9400-2
|View full text |Cite
|
Sign up to set email alerts
|

Semi-liquid metal and adhesion-selection enabled rolling and transfer (SMART) printing: A general method towards fast fabrication of flexible electronics

Abstract: Recent breakthrough in eutectic gallium-indium alloy has revealed its great potential in modern electronic engineering. Here, we established a general method towards super-fast fabrication of flexible electronics via semi-liquid metal and adhesion-selection enabled rolling and transfer (SMART) printing on various substrates. Based on the semiliquid metal and its adhesion-difference on specifically designed target materials, we demonstrated that the rolling and transfer printing method could serve to rapidly ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 47 publications
0
54
0
Order By: Relevance
“…[57] However, the adhesion of Ni-EGaIn could be controlled by the interfacial properties of different substrates. [58,59] Some research found that the wettability of a solid surface could be influenced by the chemical composition and morphological surface microstructures. [60] The scanning electron microscope (SEM) images in Figure 1f show that the morphological microstructures of nude mouse skin and PMA glue were quite different from each other.…”
Section: Fabrication and Adhesion Characterization Of Ni-egainmentioning
confidence: 99%
“…[57] However, the adhesion of Ni-EGaIn could be controlled by the interfacial properties of different substrates. [58,59] Some research found that the wettability of a solid surface could be influenced by the chemical composition and morphological surface microstructures. [60] The scanning electron microscope (SEM) images in Figure 1f show that the morphological microstructures of nude mouse skin and PMA glue were quite different from each other.…”
Section: Fabrication and Adhesion Characterization Of Ni-egainmentioning
confidence: 99%
“…However, unlike a rigid mask, a photoresist mask cannot be recycled and the process of photoetching is complex and time-consuming. Guo et al introduced toner as the mask and liquid metal could selectively adhere to area without toner [72]. A roller was applied to deposit liquid metal and the circuit could further be transferred to elastic substrate.…”
Section: Printing Technologymentioning
confidence: 99%
“…For instance, magnetism, ferromagnetic nano powders could be dispersed in liquid metal [55]. Moreover, nickel particles could be mixed with EGaIn for fast fabrication of soft electronics by direct writing or printing [70][71][72]. As shown in Figure 1B, Ni particles were wrapped by a liquid metal oxide layer after stirring for a moment.…”
mentioning
confidence: 99%
“…This results in selective wetting of EGaIn and EGaIn‐Ni amalgams as demonstrated in refs. [ 42 ] and [ 43 ] , respectively. The current work builds over these works and improves the conductivity, printing resolution, and stretchability of the printed samples.…”
Section: Introductionmentioning
confidence: 99%